Tape stripping method is useful for the quantification of antimicrobial peptides on the human skin surface including the stratum corneum - Ono, Shigeyuki (Sci Rep, 2020)
Antimicrobial peptides (AMPs) play an important role in innate immunity in human skin. It is known that AMPs mainly function in the stratum corneum. Therefore, AMP concentrations in the stratum corneum need to be precisely measured to clarify functional and physiological importance of AMPs in cutaneous defence. Tape stripping (TS) is a well-established method by which components in the stratum corneum can be collected. However, the usefulness of the TS method for measuring AMP concentration in human skin remains unclear. Therefore, we compared it with another popular method, skin rinsing, which had been established as a method for measuring AMP concentration in human skin. When investigated on healthy medial forearm using RNase 7, which is one of the typical AMPs, as an index, there was a significant positive correlation between RNase 7 concentrations measured by the TS method at adjacent forearm sites, demonstrating the reproducibility of the TS method. Next, a significant positive correlation was detected in RNase 7 concentrations measured using the TS and the skin rinsing method, indicating that the TS method is comparable to the skin rinsing method. Thus, we speculate that the TS method is useful for measuring AMP concentration in human skin.